Human-Elephant Conflict and its Possible Control Measures in South West Bengal Land Scape, India - Pandit, Prasanta Kumar; Chanda, Subhamay (Indian Forester, 2019)
Human elephant conflict (HEC) in South West (SW) Bengal viz., Purulia, Bankura and West Midnapore, has been a major administrative and social issue for the West Bengal Forest Department. The problem started in 1987 when elephant herds from Dalma Wildlife Sanctuary of Jharkhand state started migrating to Jhargram Division in the West Bengal state. Initially this was not a significant problem. Later on, the JFM movement improved the forest cover in SW Bengal, the conflict took on a serious dimension. Such change, along with an increase in the human population in the area, has led to severe HEC resulting in depredation of crops and property as well as injury and loss of human life. Several short term measures were adopted, out of which control driving of elephant herds and timely payment of compensation can give temporary results. Long-term measures require multiple collaborative approaches between other line departments, adjoining states and a comprehensive action plan.